1993
DOI: 10.7164/antibiotics.46.455
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mode of antifungal action of pradimicin antibiotics. II. D-mannopyranoside-binding site and calcium-binding site.

Abstract: Based on the structure-activity relationship data of BMY-28864 and related pradimicin derivatives, the calcium salt-forming ability and the D-mannopyranoside-speciflc visible absorption maximumshift of BMY-28864 were analysed in the ternary complex formation of BMY-28864 with D-mannopyranoside and calcium. The free C-18 carboxyl group of BMY-28864 was proved to be the sole site for binding to calcium, while no hydroxyl groups of the aglycone were involved in calcium salt formation. The stereospecific D-mannopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 1 publication
(1 reference statement)
3
51
1
Order By: Relevance
“…Since no N-glycan deletions have ever been observed in gp41 of PRM-A-resistant (8) and PRM-Sresistant (this study) virus strains, this binding to gp41 may most likely not be directly related to the eventual antiviral activity of the pradimicins. The pradimicins have been suggested to be physiologically active as a (dimeric) complex with Ca 2ϩ (17,29,30). Experimental evidence has indeed been provided that in the presence of PRM-A, (␣-1,2)mannose oligomers, and Ca 2ϩ , a ternary complex is formed that consists of one Ca 2ϩ ion, two pradimicin-A molecules and four (␣-1,2)mannose oligomers (17,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since no N-glycan deletions have ever been observed in gp41 of PRM-A-resistant (8) and PRM-Sresistant (this study) virus strains, this binding to gp41 may most likely not be directly related to the eventual antiviral activity of the pradimicins. The pradimicins have been suggested to be physiologically active as a (dimeric) complex with Ca 2ϩ (17,29,30). Experimental evidence has indeed been provided that in the presence of PRM-A, (␣-1,2)mannose oligomers, and Ca 2ϩ , a ternary complex is formed that consists of one Ca 2ϩ ion, two pradimicin-A molecules and four (␣-1,2)mannose oligomers (17,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Ca 2ϩ , PRM-A and PRM-S are unable to bind to HIV-1 gp120 in SPR experiments. Also, methylation of the free carboxylic acid of PRM-A has been demonstrated to result in complete inactivity of the antibiotic (29), suggesting that Ca 2ϩ may act as a bridging ion between the carboxylic acid groups of two PRM-A molecules. It is currently unclear whether Ca 2ϩ solely plays a role in bridging two pradimicin molecules or whether it also plays a role in coordinating mannose binding to the antibiotics, as C-type lectins seem to do.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidences indicated that another mechanism similar to benanomicins and pradimicins may be used to explain the action mode of CF66I against the fungal cell wall. These two drugs killed the fungal cells by damaging the fungal cell wall structure by forming an insoluble complex with polysaccharide (mannan) [12,13]. However, when CF66I was mixed with cell wall polysaccharides, no insoluble complex was observed, but specific binding of CF66I to β-1,6-glucan was observed and its antifungal activity changed, which maybe the reason of CF66I-inducing changes on fungal cell wall.…”
Section: Discussionmentioning
confidence: 96%